O cuidado prestado pelo enfermeiro nos Centros de Referência em Saúde Mental de Belo Horizonte - Sandra Miramar de Andrade Pinheiro (2011)
This study has the objective of analyzing the care provided by the nurse practitioner in Reference Centers for Mental Health (CERSAM, in Portuguese abbreviation) of the city of Belo Horizonte (Minas Gerais, Brazil). It sought to identify the practices of the nurse that characterize the assistance in CERSAM and the theoretical and methodological fundaments of those practices. The method used has been qualitative research, founded on the theoretical basis of Dialectic focused on the socio-historical perspective. The data collection consisted of seven interviews with nurses working in CERSAM assistance, as well as of records in form of field notes. To construct the empirical categories, it was used the technique of content analysis based on the apprehension of the themes contained in the data from the interviews. The analysis has revealed themes that made possible recognizing three empirical categories: The doing of the nurses in CERSAM, The knowledges that fundament the care by the nurse in mental health; The challenges to the nurse when providing care in mental health. The results of the study indicate that the nurses act on a technological basis that comprehends the harboring during the crisis, act as reference technicians, attend the families of patients, and perform the management of assistance to the nursery team. In their practice, they orient themselves by the fundaments of basic needs theory, the references of psychosocial rehabilitation, and the knowledge from Psychiatry, Psychoanalysis and Psychosocial Attention. Those practitioners face daily the challenge of conciliating the actions of care with the management of assistance, challenge which enables advances to the care and to the professional category.